Behind the veil: the challenges and impediments encountered by women entrepreneurs in the United Arab Emirates. (1st August 2019) - Tahir, Rizwan; Baradie, Mohamed El
Female entrepreneurship has now become a significant business trend in most countries around the globe. Nevertheless, relatively few previous studies (Itani et al., 2011) have concentrated on female entrepreneurs in Middle Eastern countries, where SMEs are perceived as the way for these countries to lessen their dependence on oil. The present study endeavours to research the female entrepreneurs in the United Arab Emirates and to examine the challenges and impediments to the advancement and development of entrepreneurial activities. Based on the results, some of the challenges that were identified as impediments to women entrepreneurs included difficulties in obtaining start-up capital, gender discrimination, lack of training and networking opportunities. Suggestions are made about how to bring about a change in the attitudes towards female and their entrepreneurial endeavours. Finally, limitations of this study as well as directions for future scholarly research are identified.